ANTIVIRAL DRUG REVIEW A GUIDE TO CLINICIANS - Eline Guerrart Portugal, Magda; Maria Raboni, Sonia (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
Over the past forty years, there has been a great advance in antiviral infections treatment. The discovery of acyclovir in 1977 paved the way to new antiviral drugs. Other nucleoside analogues such as valacyclovir, penciclovir, famciclovir, anciclovir, valganciclovir, cidofovir and foscarnet were made available, as well as neuraminidase inhibitors. Also, drugs for the treatment of viral hepatitis and patients with HIV/AIDS have not only increased life quality and expectancy, but also decreased the incidence of some viral infections. Antiviral drugs are important tools to the clinician, especially when treating patients with impaired immunological and clinical condition. Aiming to restore health and prevent further adverse events, the clinician must be aware of the best antiviral drug available, its proper route of administration and dosage. The aim of this review is to present the antiviral drugs currently available, focusing on treatment of common viral infections in clinical practice. A brief description of the mechanisms of action and prescription of antiviral drugs is presented, using the data available from evidence-based medicine.